2019 IEEE International Electric Machines &Amp; Drives Conference (IEMDC) 2019
DOI: 10.1109/iemdc.2019.8785338
|View full text |Cite
|
Sign up to set email alerts
|

High-Torque-Density Low-Cost Magnetic Gear Utilizing Hybrid Magnets and Advanced Materials

Abstract: Two major challenges of existing high-performance magnetic gears are: (i) High content of rare-earth permanent magnets which results in high cost as well as price fluctuation; (ii) Conflict between mechanical and electromagnetic performances, especially in the design of highspeed rotor. A magnetic gear using a blend of magnet types, i.e NdFeB, or Dy-free NdFeB and ferrites, is proposed in this paper. The goal is to bring down the cost while retaining comparable torque-transducing performance to a baseline magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…As a consequence, this paper aims to address foregoing PM material challenges and investigate the electromagnetic performance of blended magnet designs proposed for electric vehicles (ferrite with both Dy-NdFeB and Dy-free NdFeB) in the context of FM-MGs and MGMs as to extend the work in [59,60].…”
Section: Objective and Organization Of This Papermentioning
confidence: 99%
“…As a consequence, this paper aims to address foregoing PM material challenges and investigate the electromagnetic performance of blended magnet designs proposed for electric vehicles (ferrite with both Dy-NdFeB and Dy-free NdFeB) in the context of FM-MGs and MGMs as to extend the work in [59,60].…”
Section: Objective and Organization Of This Papermentioning
confidence: 99%
“…The mechanical strength of the MG proposed in [10] is significantly improved because of the spoke-type configuration and, it is demonstrated that this MG can achieve a comparable torque density to mechanical gears. In [11], a high-torque-density spoke-type MG was proposed, and a parameter optimization was performed to obtain the highest torque density. The hybrid utilization of PM materials was investigated in terms of the volumetric torque density (VTD), specific torque, and manufacturing cost of the MG.…”
Section: Introductionmentioning
confidence: 99%
“…AGNETIC gears have attracted much attention due to the advantages of free-of-contact, inherent overload capability, silent operation, and high reliability compared with mechanical gears [1], [2]. The coaxial magnetic gear (CMG), which comprises coaxial inner and outer rotors on the two sides of ferromagnetic segments, realizes a better utilization of PMs and transmits significantly higher torque density compared with other types of MGs [3], [4]. Therefore, CMGs have been employed in critical environments to meet the high requirement and harsh working conditions.…”
Section: Introductionmentioning
confidence: 99%